Beyond the Threshold: Emancipation or Entrapment? The Feminine Archetypes in Pakistani Women Fiction Writers - Dr. Ahmed Usman, Ambreen Salahuddin (Journal of Research in Humanities, 2023)
This paper discusses the concept of feminine archetypes with reference to the fiction produced by Pakistani women writers. The reality of spaces of women, as seen by patriarchy, is summed up in famous adages that state “it is a man’s world; woman’s place is in the home.” On the basis of “man’s world” and “woman’s place”, the paper focuses on home and the role of a woman therein. There are indeed several roles, but the focus in this paper will be on the role of a wife or ‘lady of the house’. What is expected of a wife usually sums up what is expected of a woman by the others. The expected role is that of the feminine archetype that has been focused on more and is portrayed mostly throughout literary texts. For this research, complete works of Pakistani women fiction writers, writing in six languages, have been studied. The number of writers is twenty-six.